Nonsurgical management of an extensive periapical lesion combined with photodynamic therapy: a case report - Figueirêdo Júnior, Ernani Canuto; Ataíde, Thays Chalegre; Missias, Eucaé Miranda; de Albuquerque, Mônica Soares; Torres, Renata Correia Sotero Dália (Revista de Ciências Médicas e Biológicas, 2022)
Introduction: the major goal of endodontic treatment (ET) is the complete elimination and/or maximum possible reduction of bacteria and irritants in the root canal system (RCS). However, persistence of bacterial debris refractory to therapy may leading to ET failure, being necessary to realize conventional or surgical retreatment. Objective: this is a case report on the nonsurgical management of an extensive chronic periapical lesion in teeth 12 and 11 in an adult female patient with history of endodontic treatment failure. She presented with painless swelling and a fistula adjacent to tooth 11. Methodology: conventional ET combined with photodynamic therapy (PDT) was recommended, in addition to calcium hydroxide applications. Regular clinical and radiographic follow-up made over a 2-year period revealed progression of bone regeneration, without sign and symptoms, with a satisfactory outcome. Conclusion: this case report shows that the combination of conservative ET with PDT provided satisfactory results with the resolution of the chronic endodontic infection and bone repair of the extensive periapical lesion.